Penerapan Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Ditinjau dari Aktivitas Belajar Siswa Kelas VIII SMP - Muhamad Firdaus (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2016)
The purpose of this study was to find out the results belejar junior high school students after application of cooperative learning model NHT the terms of the learning activities. Forms of research is quasy Experiment with the design of a 1x3 factorial design. The population in this study were all students of class VIII SMP Negeri 1, while the sample is a class VIII-D randomly selected using random cluster sampling technique. Data collection tool used is a test instrument that consists of four essay and activity questionnaire consisting of 23 questions. Based on analysis test, one way ANOVA with different cells obtained by (1) the learning outcomes of students with high activity category as well as students with moderate activity category. (2) the learning outcomes of students with moderate activity category better with students with low activity category. (3) the learning outcomes of students with high activity category better with students with low activity category. Keywords: Cooperative learning NHT type, learning activities